UNDANG-UNDANG PERLINDUNGAN UMAT BERAGAMA DALAM PERSPEKTIF NU - Pipin Armita (Millah: Journal of Religious Studies, 2017)
This paper distributed by many religious conflictsthat has happened in Indonesia. So,to prevent and resolve the issue, the Government has established regulations and legislation about  religious believiers protection even since the beginning of the founding the nation. However, the reality show us that religous conflict is still not over. Thus, author aim to describe and analyze NU criticism to  religious believiers protection laws in Indonesia as well as how the solution offered especially on Bahtsul Masail Muktamar NU 33th at 2015. On NU persfective, there are some things abaut religious believiers protection laws: (1) regulations and legislation about  religious believiers protection are scattering on many legistlation or regulation on under the act, so it does not focus talking about religious believiers protection only. (2) many legislation and regulation is not enough to be a foundation of nation to execute every religious conflict. (3) LITBANG reseach has proven there are seven factor that cause religious conflict. (4) some of regulations under the legislation judged is not have a strong position, because it is not included in hierarchy of legislation. Therefore, all these problems, on NU perspective proves that more existence of operacional and aplicable legislation are absolutely needed.